2014
DOI: 10.5539/ass.v10n7p213
|View full text |Cite
|
Sign up to set email alerts
|

The State of Social Studies in Basic Education Schools in Oman

Abstract: This study explored the state of social studies in basic education schools in the current reform. Particularly, it explored teachers' preferred rationales for teaching social studies, content areas emphasized in the social studies curriculum, instructional methods used by teachers, and the importance of social studies and other school subjects. Data were gathered by surveys from 451 social studies teachers from all Omani governorates. Findings showed that teachers supported all rationales for teaching social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In line with this finding, the participants stressed the importance of social studies in Omani schools as a vehicle to teach about various aspects of the pandemic along with other rationales-teaching important knowledge, skills, and values associated with the subject. Surprisingly, their view of the importance of social studies contradicts previous research findings, which reflect the view that social studies is a marginalized school subject (e.g., Al-Maamari et al, 2014;Leming et al, 2006).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In line with this finding, the participants stressed the importance of social studies in Omani schools as a vehicle to teach about various aspects of the pandemic along with other rationales-teaching important knowledge, skills, and values associated with the subject. Surprisingly, their view of the importance of social studies contradicts previous research findings, which reflect the view that social studies is a marginalized school subject (e.g., Al-Maamari et al, 2014;Leming et al, 2006).…”
Section: Discussionmentioning
confidence: 56%
“…As with other subjects, the status of social studies in Omani schools has improved since the implementation of the Basic Education Reform in 1998 (Al-Maamari et al, 2014;Al-Nofli, 2013;Ministry of Education, 2006). For example, the reform places great emphasis on student-centered approaches and continuous assessments.…”
Section: Geography and Modern Technologies (Elective) 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, teachers require some training to development their homework practice. In previous study, social studies teachers reported that they offering very limited opportunity for participate in professional development programme (Al-Maamari, Al-Nofli, & Al-Gharibi, 2014). According to Farkas, Johnson and Duffett (1999), training is the main issue that teachers complained about most and Omani teachers are not exceptional.…”
Section: Discussionmentioning
confidence: 99%
“…The social studies program for postbasic education is organized around two core subjects and four elective subjects. (Al-Gharibi, 2008;Al-Kharousi, 2014). Al-Kharousi (2014) found that post-basic education students (Grades 11-12) viewed the subject as providing fewer career opportunities than other subjects (e.g., mathematics and science).…”
Section: The Place Of Social Studies In Omani Schoolsmentioning
confidence: 99%